PENGEMBANGAN MEDIA PUZZLE UNTUK PEMBELAJARAN BIOLOGI PADA MATERI PRIMATA SISWA KELAS X SMA - Kristina Niken Pawestri; Eko Wulandari; Eni Yulianti (Pendidikan Biologi STKIP YPM Bangko, 2021)
Textbooks used are few in number so that they do not attract students interest in learning. The high level of diversity of living things and the number of similar species make it difficult for students to distinguish primates from one species to another without learning media. Moreover teacher have never developed media such as puzzle in the learning process such as puzzle to increase student interest in learning biology. Puzzle media on primates material as a learning medium for biology class X SMA Negeri 17 Merangin. This research instrument uses a validation and practicality questionnaire. This a product in form of a valid and practical puzzle in terms value of 98% (valid) and was declared value of 4,00 (practical) by teacher. So, puzzle media on primate material has been declared valid and practical.